What Can the Brand Manager Expect from Facebook?. Issue 1 (February 2018) - Sitta, Desislava; Faulkner, Margaret; Stern, Philip
Managers cannot afford to ignore social media and have stepped up their involvement in the belief that social media activities extend the brand's reach and engagement with consumers. Facebook is the preeminent social medium with an ever increasing branded content. One hundred brands selected from the Interbrand "Best Global Brand Report" form the basis of this study to test research propositions about the ability of branded Facebook pages to expand and engage users. Data captured from branded Facebook pages was supplemented with socialbaker's data. No correlation is found between the size of a brand and the number of Facebook fans, and there is no consistent relationship with user engagement and brand size. The authors discuss broadening reach, improving engagement, interaction and activity and the implications for social media strategies and make recommendations for managing Facebook presence. Paid advertising is required to increase brand reach to all potential category users.